WADY WRODZONEHepatic veins’ inclusion in the system of total cavo-pulmonary connection - Mroczek, Tomasz; Jarosz, Jerzy; Skalski, Janusz H. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Pulmonary arteriovenous malformations are a major cause of progressive late cyanosis in patients treated with cavopulmonary anastomoses. We have studied two patients with heterotaxy, univentricular congenital heart defect, and azygous continuation of the inferior vena cava who underwent successful incorporation of the hepatic veins into the cavopulmonary circuit for treatment of progressive cyanosis and circulatory failure after a Kawashima procedure. Resolution of pulmonary arteriovenous malformation after hepatic vein inclusion into the cavopulmonary circulation has been reported.